2009
DOI: 10.1007/s11430-009-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Cropland cover change in Northeast China during the past 300 years

Abstract: Land use/cover change induced by human activities has emerged as a "global" phenomenon with Earth system consequences. Northeast China is an area where the largest land cultivation activities by migrants have happened in China during the past 300 years. In this paper, methods including documentary data calibration and multi-sourced data conversion model are used to reconstruct historical cropland cover change in Northeast China during the past 300 years. It is concluded that human beings have remarkably change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 5 publications
6
77
1
Order By: Relevance
“…The total area of arable land was about 25,397 km 2 , accounting for 5.61% of Heilongjiang in this period. Our estimation is similar to that of Ye et al (2009), who estimated that 5.4% of Heilongjiang was arable land during 1900-1910. This estimated fraction of cropland area at the county level has a spatial pattern characterized by more cropland in the center of the province and less cropland in the surrounding areas.…”
Section: Methods Of Retrieving Area Of Cropland In 2009supporting
confidence: 89%
See 4 more Smart Citations
“…The total area of arable land was about 25,397 km 2 , accounting for 5.61% of Heilongjiang in this period. Our estimation is similar to that of Ye et al (2009), who estimated that 5.4% of Heilongjiang was arable land during 1900-1910. This estimated fraction of cropland area at the county level has a spatial pattern characterized by more cropland in the center of the province and less cropland in the surrounding areas.…”
Section: Methods Of Retrieving Area Of Cropland In 2009supporting
confidence: 89%
“…Other areas, especially the northern and eastern parts of the study area, were much less developed. Ye et al (2009) have reported the spatial distribution of cropland at the county level based on the present county boundaries. To compare our results with those of Ye et al (2009), we recalculated the fraction of cropland area at the county level based on the present counties using our reconstructed data.…”
Section: Methods Of Retrieving Area Of Cropland In 2009mentioning
confidence: 99%
See 3 more Smart Citations